Histopathological Changes of Heart, Liver, and Duodenum in Iron Overload: ‎Comparing the Role of Quercetin with Deferoxamine - A Awad, Muntasser; Al-Okaily, Baraa (The Iraqi Journal of Veterinary Medicine, 2023)
The aim of this study was to perform a comparison between quercetin and deferoxamine (DFO) ‎on the heart, liver, and duodenum in iron overloaded rabbits. Four groups of adult rabbits (each ‎of seven) used in the current study were treated as follows for 28 days: control (C): were ‎injected intraperitoneally (IP) normal saline every 72 hours + normal saline orally daily. T1, ‎T2, and T3 groups were IP injected with iron dextran 100 mg/kg every 72 hours, T1 was left ‎without treatment, group T2 was administrated with quercetin 350 mg/kg orally daily, and ‎group T3 was injected with DFO 125 mg/kg intramuscularly (IM) daily. At the end of ‎experiment, all animals were sacrificed, and tissue specimens were collected from the heart, ‎liver, and duodenum for histopathological study. The results of T1 group showed edema, and ‎iron deposition between the myocardial cells. The T2 group showed slight edema between the ‎myocardium. T3 group showed edema, thickening, and congestion of blood vessels, all groups ‎showed a positive result of the Prussian blue stain (PBS) compared to the control. The liver ‎sections for the T1 group revealed iron overload, fibrosis, and hepatocyte necrosis. T2 and T3 ‎groups showed mild vacuolation of hepatocytes, a decrease in iron overload, and these groups ‎showed a positive result of the PBS compared to the control. Duodenum sections for T1 group ‎showed hemochromatosis. while T2 group showed mild iron deposition. Positive result of PBS ‎in T1 and T3 compared to the T2 and control were observed. Conclusion: Quercetin mitigates ‎histological changes in iron overloaded rabbits due to its properties as an iron chelating agent ‎compared to DFO‎.